2014
DOI: 10.1186/1472-6882-14-221
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of hematopoietic prostaglandin D2 Synthase (H-PGDS) by an alkaloid extract from Combretum molle

Abstract: BackgroundHematopoietic prostaglandin D2 synthase (H-PGDS, GST Sigma) is a member of the glutathione S-transferase super family of enzymes that catalyses the conjugation of electrophilic substances with reduced glutathione. The enzyme catalyses the conversion of PGH2 to PGD2 which mediates inflammatory responses. The inhibition of H-PGDS is of importance in alleviating damage to tissues due to unwarranted synthesis of PGD2. Combretum molle has been used in African ethno medicinal practices and has been shown t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Chemicals with antioxidant properties have the capacity to induce glutathione transferases in vitro and in vivo through the bZIP transcription factor (Nrf2) and the antioxidant response element (ARE) [ 36 , 37 ]. Moyo et al, [ 38 ] showed that another Combretum species, Combretum molle inhibited human recombinant hematopoietic prostaglandin D2 synthase (GST sigma) in vitro, an enzyme that is involved in the synthesis of prostaglandin D2. Combretum leprosum -derived triterpenes have been shown to have anti-inflammatory effects in mice [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chemicals with antioxidant properties have the capacity to induce glutathione transferases in vitro and in vivo through the bZIP transcription factor (Nrf2) and the antioxidant response element (ARE) [ 36 , 37 ]. Moyo et al, [ 38 ] showed that another Combretum species, Combretum molle inhibited human recombinant hematopoietic prostaglandin D2 synthase (GST sigma) in vitro, an enzyme that is involved in the synthesis of prostaglandin D2. Combretum leprosum -derived triterpenes have been shown to have anti-inflammatory effects in mice [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, genes associated with GST activity ( gstk-1 ) and glutathione peroxidase activity ( pgx-7 ) were significantly downregulated in nimodipine-treated CL2355 worms as compared to untreated controls. HPGDS (GST Sigma) catalyzes glutathione conjugation to molecules and plays a role in prostaglandin D2 biosynthesis, associated with the inflammatory response [ 33 , 34 ]. GST is a large family generally involved in detoxification and removal of oxidative stress.…”
Section: Resultsmentioning
confidence: 99%
“…L-PGDS is a monomeric protein present in several mammalian central nervous system tissues and the male genital organs; in contrary, it is abundant in cerebrospinal fluid [60]. Hematopoietic prostaglandin D synthase (H-PGDS) is a member of the sigma-class of glutathione-S-transferases (GST) [61]. H-PGDS is expressed in various immune and inflammatory cells, such as mast cells in rat model and type 2 T lymphocytes in human cell lines [62,63].…”
Section: Discussionmentioning
confidence: 99%